Coastal Boulders on the SE Coasts of Cyprus as Evidence of Palaeotsunami Events. - Evelpidou, N.; Zerefos, C.; Synolakis, C.; Repapis, C; Karkani, A.; Polidorou, M.; Saitis, G. (Journal of Marine Science and Engineering, 2020)
Cyprus has a long history of tsunami events, as noted by archaeological and geological records. At Cape Greco (southeastern Cyprus) large boulders have been noted, however, no detailed geomorphological research has taken place so far and the related high energy event was undated until now. Our research aims to record in detail and interpret these large boulders deposits. The boulders, located between ≈3 and 4.5 m a.m.s.l., are fragments of an upper Pleistocene aeolianite, which is overlaying unconformly a lower Pleistocene calcarenite. Dimensions and spatial distribution of 272 small, medium, and large boulders were documented, while their precise distance from the coastline was recorded by field mapping and remote sensing, using Differential GPS (DGPS), drone, and Geographic Information Systems (GIS) technics. Field data were subsequently combined with hydrodynamic equations, in order to determine the extreme event(s) that caused their transport inland, and radiocarbon dating was accomplished on three samples of Vermetus sp. to determine the chronological context. Our findings appear to broadly correlate with the 1303 AD tsunami, which has displaced at least part of the studied boulders, and one other undocumented event at AD 1512-1824. The large number of boulders and sizes in our study area further indicate that their dislocation is most likely owed to multiple events from various sources.